ANALISIS BREAK EVEN POINT DAN MARGIN OF SAFETY SEBAGAI ALAT PERENCANAAN LABA PADA UD. BUDI JAYA MAKMUR LAMONGAN - Arrizqi, M. Sawadil; Mulyati, Diana; Maruta, IGN Anom (Universitas 17 Agustus 1945 Surabaya, 2020)
ABSTRAK It requires the proper management ability to see opportunities in the future. Hence, it is essential to take into account all the factors associated with cost, volume, and selling price. The purpose of this study was to determine the magnitude of the break-even point and the margin of safety in planning profits at UD. Budi Jaya Makmur. If the break-even point value and the value of the margin of safety are high, then the company is in good condition, or it will be easier to relate to its efforts to generate profits. However, when break-even point values and the value of the margin of safety in lousy, these values will apply otherwise.This research used quantitative methods that the data analysis performed by measuring the pattern of cost and sales volume development using time series analysis; break-even points analysis and margin of safety. The data supported by company data collected such as cost and sales data which had previously classified as cost and contribution distribution.The analysis shows that the break-even point value for 2020 is Rp.168,410,338 and for 2021 it’s Rp.172,961,248. The margin of safety for 2020 is 52.75%, and for 2021 it’s 53.23%, this means that if the actual sales of Kerupuk Terasi from UD. Budi Jaya Makmur are less than 52.75% in 2020 and 53.23% in 2021 from planned sales, the company will suffer losses. The profit margin is set at 20% so the company must reach sales of Rp.356,412,200 in 2020 and Rp.369,825,380 in 2021. Keyword : Forecasting, Break Even Analysis, Margin of Safety.